Creation, abrogation and application of precedents: An analysis of chilean constitutional precedents related to unborn - Nuñez Vaquero, Alvaro (2021)
The objective of this work is to analyze the conditions of creation, abrogation and application of the precedents. For this, we will take as a reference the jurisprudence of the Chilean Constitutional Court on theprotection of unborn babies. We will proceed as follows: first, an introduction to the problem is made. Secondly, the Chilean constitutional precedents on the matter are presented. Third, the basic terms to understand the problem will be defined: precedent, stare decisis and ratio decidendi. Fourth, some of the rules most frequently present in our legal systems that regulate the existence of precedents are exposed. Fifth, the different types of abrogation of precedents are presented, analyzing whether any of the precedents of the Chilean discussion have been eliminated. Sixth, we will address the criteria of applicability in the face of incompatible precedents. The article ends with a few brief conclusions.